2020
DOI: 10.3390/cancers12051248
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Modal PET and MR Imaging in the Hen’s Egg Test-Chorioallantoic Membrane (HET-CAM) Model for Initial In Vivo Testing of Target-Specific Radioligands

Abstract: The validation of novel target-specific radioligands requires animal experiments mostly using mice with xenografts. A pre-selection based on a simpler in vivo model would allow to reduce the number of animal experiments, in accordance with the 3Rs principles (reduction, replacement, refinement). In this respect, the chick embryo or hen’s egg test–chorioallantoic membrane (HET-CAM) model is of special interest, as it is not considered an animal until day 17. Thus, we evaluated the feasibility of quantitative an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 87 publications
1
24
0
Order By: Relevance
“…Moreover, the addition of CT or MRI scans to PET could provide relatively accurate tumor volume estimation, as in ovo/vivo CT and ex ovo/vivo CT scans of the tumor were found to be comparable. In a similar manner, this was also the case for PET/MRI scans, where target-specificity was evaluated in ovo for prostate-specific membrane antigen (PSMA) positive and negative prostate carcinoma xenografts (Figure 3(b)) [99]. Previous mouse xenograft studies using the same PSMA-specific tracer demonstrated comparable accumulation values for both mice and CAM models.…”
Section: Applications In Imaging and Detectionmentioning
confidence: 74%
See 1 more Smart Citation
“…Moreover, the addition of CT or MRI scans to PET could provide relatively accurate tumor volume estimation, as in ovo/vivo CT and ex ovo/vivo CT scans of the tumor were found to be comparable. In a similar manner, this was also the case for PET/MRI scans, where target-specificity was evaluated in ovo for prostate-specific membrane antigen (PSMA) positive and negative prostate carcinoma xenografts (Figure 3(b)) [99]. Previous mouse xenograft studies using the same PSMA-specific tracer demonstrated comparable accumulation values for both mice and CAM models.…”
Section: Applications In Imaging and Detectionmentioning
confidence: 74%
“…To obtain high-resolution images, motion artifacts due to sudden movements of the chick embryo should be prevented. Anesthetics have been delivered to the chick embryo through fumigation or topical administration [98][99][100]. Alternatively, eggs could be pre-cooled at 4°C for at least 1 hour prior to imaging [83].…”
Section: Applications In Imaging and Detectionmentioning
confidence: 99%
“…It is worth noting that the HET-CAM method represents a potential alternative to animal experiments to assess toxicity and is widely applied to replace animal experiments. 42 In our HET-CAM assay, we observed hemorrhage from blood vessels that started within 2-4 seconds after applying 1% sodium dodecyl sulfate (SDS) as positive control. Lysis occurred after 27 seconds, and we observed coagulation within 24 hours.…”
mentioning
confidence: 92%
“…These remained in the optical and spin active state (NV − ), which is essential for applications of ND-CP in bioimaging, tracking, and nanoscale sensing. The biocompatibility of ND-CP was investigated using HeLa cell line as well as in a chorioallantoic membrane (HET-CAM) ex vivo model 42 . As depicted in Figure 3B, the ND-CP showed low cytotoxicity upon treating cells at high concentrations of up to 200 µg/mL.…”
mentioning
confidence: 99%
“…Finally, another alternative PDX platform is provided in the contribution by Winter et al [ 11 ] using the Hen’s egg test–chorioallantoic membrane (HET–CAM) PDX model. Like the ZF embryo, the chicken embryo lacks a functional immune system and is considered a non-life animal, making these PDX models an attractive platform for (“non-animal”) drug testing.…”
mentioning
confidence: 99%